Screening of Secondary Metabolites Compounds in Stem Bark of Frangipangi (Plumeria alba) and Toxicity Test on Shrimp Larvae (Brine Shrimp Lethality Test) - Santi Nur Handayani; Moch. Chasani (EKSAKTA: Journal of Sciences and Data Analysis, 2011)
Frangipani  is  a  plant  belonging  to  the  family  Apocynacea  and  potential  for development as anti-cancer drug material. Content of secondary metabolites, anti-cancer compounds from frangipani (Plumeria alba) steam bark, especially it has not been made. This  research aims  to  identify compounds  secondary metabolites  from  frangipani  steam bark extract potential for development as anti-cancer drug material. Steps undertaken in this study include:  Extraction of secondary metabolites with frangipani  stem  bark  maceration  method  of  storey  with  n-hexane,  chloroform,  ethyl acetate, and ethanol. Each tested extracts obtained using prawn shrimp toxicity A. salina Leach  and  continued  with  the  testing  of  secondary  metabolites  using  color  reagents. fraction  extract  has  potential  as  an  anti-cancer  drugs  is  purified  using  gravity  column chromatography  technique  with  elusi  gradient  technique  using  a  solvent  mixture  n-hexane:ethyl acetate hen conducted toxicity tests followed by identification using GC-MS  Extraction  results obtained by  the  four extracts namely: n-hexane extract  (E1)  is positive flavonoid groups, chloroform extract (E2), ethyl acetate extract (E3) and ethanol extract (E4)  is positive for secondary metabolite groups flavonoid and alkaloid. Toxicity test results obtained LC50 values respectively participated: 973. 7 ppm (E1), 451.35 ppm (E2), 112.557 ppm(E3), and 637.50 ppm(E4).   Keywords: Plumeria alba, secondary metabolite, toxicity test, and A. salina Leach